THE ROLE OF EDUCATION AS A PREVENTIVE MEASURE AGAINST EARLY MARRIAGE: A FAMILY LAW PERSPECTIVE - Dahlan, Muhammad Fitratallah; Dahlan, Muh. (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The issue of child marriage and education are closely interconnected. One of the factors contributing to the increasing number of marriage dispensation requests for minors is the lack of access to education, particularly among children who drop out of school due to financial limitations.The article aims to analyze the role of education in reducing the number of marriage dispensation requests for minors. It focuses on emphasizing the importance of education in preventing early marriages and promoting better decision-making among children. The study employs a doctrinal method using a qualitative legal research approach. It examines existing legal frameworks and educational factors related to child marriage in Indonesia. The research reveals that education plays a significant role in reducing marriage dispensation requests by equipping children with a better understanding of marriage and its implications. This empowers them to make more informed decisions. The study also suggests that the government should review and strengthen legal protections while ensuring the right to education for children to help address this issue.